Times of transition: Judea in the early Hellenistic period - Honigman, Sylvie; Honigman, Sylvie; Nihan, Christophe; Nihan, Christophe; Lipshits, ʿOded; Lipshits, ʿOded; Berlin, Andrea M.; Chrubasik, Boris; Farhi, Yoav; Gadot, Yuval; Gambash, Gil; Garfinḳel, Yosef; et al. (Mosaics, 2021)
Frontmatter -- Contents -- Abbreviations -- Contributors -- Preface -- Introduction -- I. The Chronological Frame, Politics and Identity -- 1. The Ptolemaic Period: A Dark Age in Jewish History? -- 2. Numismatic Evidence and the Chronology of the Fifth Syrian War -- 3. The Representation of the Victorious King -- 4. Aramaic, Paleo-Hebrew and “Jewish” Scripts in the Ptolemaic Period -- II. The History of Rural Settlement in Judea -- 5. Judah in the Early Hellenistic Period: An Archaeological Perspective -- 6. Khirbet Qeiyafa in the Late Persian and Early Hellenistic Periods -- 7. Coin Circulation in Judea during the Persian–Hellenistic Transition -- 8. Political Trends as Reflected in the Material Culture -- III. The Workings of Empires in Local and Comparative Perspectives -- 9. The Harbor of Akko-Ptolemaïs: Dates and Functions -- 10. The Achaemenid–Ptolemaic Transition -- 11. Sanctuaries, Priest-Dynasts and the Seleukid Empire -- 12. Gods in the Gray Zone -- 13. Sacred and Secular Activities in the Egyptian Temple Precincts (temenē) in the 3rd Century BCE -- 14. Searching for the Social Location of Literate Judean Elites in Early Hellenistic Times -- IV. The Pentateuch: Early Greek Translations and Receptions -- 15. The Idealization of Ptolemaic Kingship in the Legend of the Origins of the Septuagint -- 16. The Production of Greek Books in Alexandrian Judaism -- 17. The Septuagint: Translating and Adapting the Torah to the 3rd Century BCE -- 18. Greek Historians on Jews and Judaism in the 3rd Century BCE -- V. Biblical Texts in the 3rd Century BCE -- 19. How to Identify a Ptolemaic Period Text in the Hebrew Bible -- 20. No Prophetic Texts from the Hellenistic Period? -- 21. The Social Setting and Purpose of Early Judean Apocalyptic Literature -- 22. “To be destroyed, to be killed, and to be annihilated” (Esther 7:4) -- Index of Ancient Sources -- Index of Geographical Names -- Index of Subjects -- Index of Modern Authors